Rs46522 in the Ubiquitin-Conjugating Enzyme E2Z Gene Is Associated with the Risk of Coronary Artery Disease in Individuals of Chinese Han Population with Type 2 Diabetes - Difei Lu; Jia Huang; Xiaowei Ma; Nan Gu; Junqing Zhang; Hong Zhang; Xiaohui Guo (Journal of Diabetes Research, 2017)
Aims. We investigated the association between ubiquitin-conjugating enzyme E2Z (UBE2Z) gene SNP rs46522 and the risk of CAD in a Chinese Han population with type 2 diabetes and explored a possible interactive effect with environmental risk factors of CAD. Methods. 665 patients with T2D were enrolled; 390 were CAD patients and 275 were non-CAD patients. Genotype analysis of rs46522 (T>C) was performed using PCR-RFLP. Results. The SNP rs47522 was associated with the risk of CAD supposing recessive inheritance model (TT versus CC+CT, OR′=1.277, 95%CI′ 1.039–1.570, p′=0.020) and codominant model (TT versus CT, OR′=1.673, 95%CI′ 1.088–2.570, p′=0.019) after adjustment for confounders of CAD. A synergistic effect of rs46522 and BMI was discovered (β=0.012, p for interreaction = 0.028). In subgroup analysis, minor allele T was significantly associated with CAD in overweight and obesity subgroup (p=0.034), and the association was also proved in recessive model (OR=1.537, 95%CI 1.075–2.196, p=0.018). Smokers with genotype TT had threefold risk of CAD in comparison to nonsmokers with genotype TC or CC (p<0.001). Conclusions. The SNP rs46522 in UBE2Z gene is associated with the risk of CAD in the individuals of Chinese Han descent with type 2 diabetes and is of synergistic effect with BMI.